Wittgensteinian Fideism vs. Classical Theism - Salvatore, Nicola Claudio (Universidad de Costa Rica, 2020)
In this paper, we will present and discuss Wittgenstein´s views on religious beliefs, in order to see if and to what extent they give a plausible account of religious belief and their epistemic status. In the first part of this work, we will present and discuss Wittgenstein´s views on the subject, while in the rest of the paper we aim to show that Wittgenstein´s treatment of religious belief might lead to a number of unpalatable conclusions.